Exploring teachers' attitudes: knowledge and classroom strategies for children who stutter in New Zealand. (2nd January 2021) - Hearne, Anna; Miles, Anna; Douglas, Jill; Carr, Brendan; Nicholls, James Robert; Bullock, Melanie Sarah; Pang, Voon; Southwood, Helen
ABSTRACT : Background: Stuttering is associated with negative stereotypes and attitudes. Teachers play a pivotal role in children's lives but need to be well educated about stuttering in order to support children in the classroom. This study (i) explored New Zealand teachers' attitudes and knowledge and (ii) piloted an online education package for teachers. Method: In phase one, 59 teachers (35 primary and 24 secondary) completed an online survey examining their attitudes and knowledge of stuttering and strategies for classroom management. In phase two, 27 primary school teachers completed a short online education package including a fact sheet and educational video 'Wait wait … I'm not finished yet' (Michael Palin Centre, 2018). Teachers completed the Public Opinion Survey of Human Attributes-Stuttering POSHA-S [Abdalla, F. A., & Louis, K. O. S. (2012). Arab school teachers' knowledge, beliefs and reactions regarding stuttering. Journal of Fluency Disorders, 37(1), 54–69 ] before and after the education package. Results: The teachers surveyed had a wide range of teaching experience (1—46 years) and displayed positive attitudes to stuttering. They had gaps in their knowledge about the cause of stuttering. Teachers frequently rated 'unsure' to statements relating to the use of classroom strategies. The online education package was well received and considered valuable in understanding stuttering. Attitudes and knowledge shifted in accuracy and certainty. Conclusion: The New Zealand teachers in this study had positive attitudes but knowledge gaps. Their toolbox of appropriate classroom strategies was limited. A short online education package can enable teachers to make a positive shift in attitudes and knowledge and reflect on new strategies to use in their current classrooms. Stuttering resources should be available to all teachers .